Kingship and Queenship in the Ancient Near Eastern Empires of the 1st Millennium BCE: The Economic Basis (Enki & Ptah. Journal of Technology and Trade in Ancient Egypt and Western Asia, 2025)
The institution of kingship, and to a much lesser degree of queenship, has long been of major interest to ancient historians. However, the focus is usually on a single empire or on a comparison between two or three empires, e.g., the Neo-Assyrian and the Roman ones. This paper provides a consistent diachronical comparison over a millennium on the economic basis of the social institution across seven major empires (Neo-Assyrian, Neo-Babylonian, Teispid-Achaemenid, Seleukid, Ptolemaic, Arsacid, and Roman) with geographical as well as chronological overlap. It further includes systematically kingship as well as queenship, explicates the scope of available sources, and explores the distinction between ‘state’ and ‘royal’ assets (and expenses) to a hitherto unprecedented degree. This elicits important insights into the long-durée dynamics regarding the roles of the ‘head-of-state’ and the ‘leading lady’ within the economic systems of the ancient Near Eastern empires of the 1st millennium BCE.